src/HOL/Library/Binomial.thy
author haftmann
Tue Dec 18 14:37:00 2007 +0100 (2007-12-18)
changeset 25691 8f8d83af100a
parent 25594 43c718438f9f
child 27368 9f90ac19e32b
permissions -rw-r--r--
switched from PreList to ATP_Linkup
     1 (*  Title:      HOL/Binomial.thy
     2     ID:         $Id$
     3     Author:     Lawrence C Paulson
     4     Copyright   1997  University of Cambridge
     5 *)
     6 
     7 header {* Binomial Coefficients *}
     8 
     9 theory Binomial
    10 imports ATP_Linkup
    11 begin
    12 
    13 text {* This development is based on the work of Andy Gordon and
    14   Florian Kammueller. *}
    15 
    16 consts
    17   binomial :: "nat \<Rightarrow> nat \<Rightarrow> nat"      (infixl "choose" 65)
    18 primrec
    19   binomial_0: "(0 choose k) = (if k = 0 then 1 else 0)"
    20   binomial_Suc: "(Suc n choose k) =
    21                  (if k = 0 then 1 else (n choose (k - 1)) + (n choose k))"
    22 
    23 lemma binomial_n_0 [simp]: "(n choose 0) = 1"
    24 by (cases n) simp_all
    25 
    26 lemma binomial_0_Suc [simp]: "(0 choose Suc k) = 0"
    27 by simp
    28 
    29 lemma binomial_Suc_Suc [simp]:
    30   "(Suc n choose Suc k) = (n choose k) + (n choose Suc k)"
    31 by simp
    32 
    33 lemma binomial_eq_0: "!!k. n < k ==> (n choose k) = 0"
    34 by (induct n) auto
    35 
    36 declare binomial_0 [simp del] binomial_Suc [simp del]
    37 
    38 lemma binomial_n_n [simp]: "(n choose n) = 1"
    39 by (induct n) (simp_all add: binomial_eq_0)
    40 
    41 lemma binomial_Suc_n [simp]: "(Suc n choose n) = Suc n"
    42 by (induct n) simp_all
    43 
    44 lemma binomial_1 [simp]: "(n choose Suc 0) = n"
    45 by (induct n) simp_all
    46 
    47 lemma zero_less_binomial: "k \<le> n ==> (n choose k) > 0"
    48 by (induct n k rule: diff_induct) simp_all
    49 
    50 lemma binomial_eq_0_iff: "(n choose k = 0) = (n<k)"
    51 apply (safe intro!: binomial_eq_0)
    52 apply (erule contrapos_pp)
    53 apply (simp add: zero_less_binomial)
    54 done
    55 
    56 lemma zero_less_binomial_iff: "(n choose k > 0) = (k\<le>n)"
    57 by(simp add: linorder_not_less binomial_eq_0_iff neq0_conv[symmetric]
    58         del:neq0_conv)
    59 
    60 (*Might be more useful if re-oriented*)
    61 lemma Suc_times_binomial_eq:
    62   "!!k. k \<le> n ==> Suc n * (n choose k) = (Suc n choose Suc k) * Suc k"
    63 apply (induct n)
    64 apply (simp add: binomial_0)
    65 apply (case_tac k)
    66 apply (auto simp add: add_mult_distrib add_mult_distrib2 le_Suc_eq
    67     binomial_eq_0)
    68 done
    69 
    70 text{*This is the well-known version, but it's harder to use because of the
    71   need to reason about division.*}
    72 lemma binomial_Suc_Suc_eq_times:
    73     "k \<le> n ==> (Suc n choose Suc k) = (Suc n * (n choose k)) div Suc k"
    74   by (simp add: Suc_times_binomial_eq div_mult_self_is_m zero_less_Suc
    75     del: mult_Suc mult_Suc_right)
    76 
    77 text{*Another version, with -1 instead of Suc.*}
    78 lemma times_binomial_minus1_eq:
    79     "[|k \<le> n;  0<k|] ==> (n choose k) * k = n * ((n - 1) choose (k - 1))"
    80   apply (cut_tac n = "n - 1" and k = "k - 1" in Suc_times_binomial_eq)
    81   apply (simp split add: nat_diff_split, auto)
    82   done
    83 
    84 
    85 subsection {* Theorems about @{text "choose"} *}
    86 
    87 text {*
    88   \medskip Basic theorem about @{text "choose"}.  By Florian
    89   Kamm\"uller, tidied by LCP.
    90 *}
    91 
    92 lemma card_s_0_eq_empty:
    93     "finite A ==> card {B. B \<subseteq> A & card B = 0} = 1"
    94   apply (simp cong add: conj_cong add: finite_subset [THEN card_0_eq])
    95   apply (simp cong add: rev_conj_cong)
    96   done
    97 
    98 lemma choose_deconstruct: "finite M ==> x \<notin> M
    99   ==> {s. s <= insert x M & card(s) = Suc k}
   100        = {s. s <= M & card(s) = Suc k} Un
   101          {s. EX t. t <= M & card(t) = k & s = insert x t}"
   102   apply safe
   103    apply (auto intro: finite_subset [THEN card_insert_disjoint])
   104   apply (drule_tac x = "xa - {x}" in spec)
   105   apply (subgoal_tac "x \<notin> xa", auto)
   106   apply (erule rev_mp, subst card_Diff_singleton)
   107   apply (auto intro: finite_subset)
   108   done
   109 
   110 text{*There are as many subsets of @{term A} having cardinality @{term k}
   111  as there are sets obtained from the former by inserting a fixed element
   112  @{term x} into each.*}
   113 lemma constr_bij:
   114    "[|finite A; x \<notin> A|] ==>
   115     card {B. EX C. C <= A & card(C) = k & B = insert x C} =
   116     card {B. B <= A & card(B) = k}"
   117   apply (rule_tac f = "%s. s - {x}" and g = "insert x" in card_bij_eq)
   118        apply (auto elim!: equalityE simp add: inj_on_def)
   119     apply (subst Diff_insert0, auto)
   120    txt {* finiteness of the two sets *}
   121    apply (rule_tac [2] B = "Pow (A)" in finite_subset)
   122    apply (rule_tac B = "Pow (insert x A)" in finite_subset)
   123    apply fast+
   124   done
   125 
   126 text {*
   127   Main theorem: combinatorial statement about number of subsets of a set.
   128 *}
   129 
   130 lemma n_sub_lemma:
   131     "!!A. finite A ==> card {B. B <= A & card B = k} = (card A choose k)"
   132   apply (induct k)
   133    apply (simp add: card_s_0_eq_empty, atomize)
   134   apply (rotate_tac -1, erule finite_induct)
   135    apply (simp_all (no_asm_simp) cong add: conj_cong
   136      add: card_s_0_eq_empty choose_deconstruct)
   137   apply (subst card_Un_disjoint)
   138      prefer 4 apply (force simp add: constr_bij)
   139     prefer 3 apply force
   140    prefer 2 apply (blast intro: finite_Pow_iff [THEN iffD2]
   141      finite_subset [of _ "Pow (insert x F)", standard])
   142   apply (blast intro: finite_Pow_iff [THEN iffD2, THEN [2] finite_subset])
   143   done
   144 
   145 theorem n_subsets:
   146     "finite A ==> card {B. B <= A & card B = k} = (card A choose k)"
   147   by (simp add: n_sub_lemma)
   148 
   149 
   150 text{* The binomial theorem (courtesy of Tobias Nipkow): *}
   151 
   152 theorem binomial: "(a+b::nat)^n = (\<Sum>k=0..n. (n choose k) * a^k * b^(n-k))"
   153 proof (induct n)
   154   case 0 thus ?case by simp
   155 next
   156   case (Suc n)
   157   have decomp: "{0..n+1} = {0} \<union> {n+1} \<union> {1..n}"
   158     by (auto simp add:atLeastAtMost_def atLeast_def atMost_def)
   159   have decomp2: "{0..n} = {0} \<union> {1..n}"
   160     by (auto simp add:atLeastAtMost_def atLeast_def atMost_def)
   161   have "(a+b::nat)^(n+1) = (a+b) * (\<Sum>k=0..n. (n choose k) * a^k * b^(n-k))"
   162     using Suc by simp
   163   also have "\<dots> =  a*(\<Sum>k=0..n. (n choose k) * a^k * b^(n-k)) +
   164                    b*(\<Sum>k=0..n. (n choose k) * a^k * b^(n-k))"
   165     by (rule nat_distrib)
   166   also have "\<dots> = (\<Sum>k=0..n. (n choose k) * a^(k+1) * b^(n-k)) +
   167                   (\<Sum>k=0..n. (n choose k) * a^k * b^(n-k+1))"
   168     by (simp add: setsum_right_distrib mult_ac)
   169   also have "\<dots> = (\<Sum>k=0..n. (n choose k) * a^k * b^(n+1-k)) +
   170                   (\<Sum>k=1..n+1. (n choose (k - 1)) * a^k * b^(n+1-k))"
   171     by (simp add:setsum_shift_bounds_cl_Suc_ivl Suc_diff_le
   172              del:setsum_cl_ivl_Suc)
   173   also have "\<dots> = a^(n+1) + b^(n+1) +
   174                   (\<Sum>k=1..n. (n choose (k - 1)) * a^k * b^(n+1-k)) +
   175                   (\<Sum>k=1..n. (n choose k) * a^k * b^(n+1-k))"
   176     by (simp add: decomp2)
   177   also have
   178       "\<dots> = a^(n+1) + b^(n+1) + (\<Sum>k=1..n. (n+1 choose k) * a^k * b^(n+1-k))"
   179     by (simp add: nat_distrib setsum_addf binomial.simps)
   180   also have "\<dots> = (\<Sum>k=0..n+1. (n+1 choose k) * a^k * b^(n+1-k))"
   181     using decomp by simp
   182   finally show ?case by simp
   183 qed
   184 
   185 end